TEST ITEMS AND CURRICULUM BACKGROUND AS FACTORS WHICH INFLUENCE RESULTS IN EVALUATING LEARNING IN HIGH SCHOOL GENERAL SCIENCE. - Reiner, William B. (Science Education, 1954)
The article presents the findings of a study concerning the use of test items and curriculum background as determining factors in evaluating the learning of academic high school pupils and the vocational high school pupils in general science. In the analysis using the curriculum background of the participating pupils, a significant difference has been found out by the researchers as opposed to the findings of the statistical analysis indicating the superiority of the academic pupils over the vocational high school pupils. Furthermore, the test examination also revealed that one of the two sub-groups was in a more favored position, by virtue of its curriculum experiences, to achieve better results. Thus, careful interpretation of statistical findings is recommended by the researchers.